Allocation of R&D grants in the business sector - Martin Falk; Roger Svensson (Research Institute of Industrial Economics (IFN), 2018)
The aim of this paper is to provide new empirical evidence on the most crucial determinants of success for firms applying for public R&D grants. Previous studies have been limited to firm level data and mainly tested how firm characteristics affect the allocation of R&D grants. Thereby, they cannot differentiate between firms that have applied for grants but been rejected and firms that did not apply at all. Our contribution is that we use a detailed database of accepted and rejected R&D applications and also introduce several measures of quality indicators of R&D project applications. The estimates show that R&D projects that are assessed with good or very good ratings are significantly more likely to receive approval; particularly for innovative content and novelty as well as to expected additional impacts on R&D activities. In contrast to previous studies, most firm-level characteristics (R&D intensity, labor productivity, cash flow, industry affiliation) are not relevant, indicating that the R&D funding agency does not discriminate among different types of firms. Consequently, applicant firms should focus on radical, new and innovative ideas in their applications rather than on minor improvements.
Keywords: H25; O32; O38; 330; Government R&D-funding; Business sector; Evaluation criteria